Preparation method and application of fluorine-free anti-siphon microfiber leather
The preparation of fluorine-free waterproofing agent by copolymerizing long-chain alkyl acrylate monomers has solved the problem of poor waterproofing performance of ultra-fiber leather, achieved efficient waterproofing effect, and avoided environmental and health hazards of fluorine-containing substances, which is of commercial value.
Patent Information
- Application Number
- CN202411747173.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing ultra-fiber leather has poor waterproof performance, mainly due to its porous structure, which makes it difficult for waterproofing agents to penetrate into the fabric. Fluorine-containing waterproofing agents will produce difficult-to-degrade organic pollutants during the production process, which will harm the environment and human health.
The fluorine-free waterproofing agent is prepared by copolymerizing long-chain alkyl acrylate monomers. The non-fluorine composition is formed by mixing a non-fluorine copolymer emulsion and an aqueous polyurethane composition, which imparts stable low surface energy to the ultra-fiber leather base cloth and improves its waterproof performance.
It realizes the long-lasting, stable and low surface energy of the microfiber leather base cloth, significantly improves its waterproof performance, avoids the harm of fluorine-containing substances to the environment and health, and has commercial value and favored by consumers.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the field of ultra-fine leather, and in particular to a preparation method and application of fluorine-free anti-siphon ultra-fine leather. Background Art
[0002] With the rise of outdoor sports and people's emphasis on health and safety protection, the market demand for water-repellent textiles is growing, and the scale of related industries exceeds 100 billion yuan. At present, the waterproofing agents used in the production of water-repellent textiles are mainly fluorine-based waterproofing agents, but the production process of these high-performance fluorinated derivatives inevitably brings perfluorooctanoic acid (PFOA) or perfluorooctane sulfonic acid (PFOS) residues, which are one of the most difficult to degrade organic pollutants found in the world. They are bioaccumulative and have long-range migration, and are difficult to continue to degrade in the natural environment, which poses a great threat to human health and the living environment. As early as 2012, the Stockholm Convention on Persistent Organic Pollutants had included PFOA and PFOS in the list of chemicals to be banned, and a comprehensive ban has become a general trend.
[0003] Microfiber leather, also known as ultrafine fiber leather, is composed of nylon ultrafine fiber and polyurethane. It has the inherent moisture absorption and breathability of natural leather, and at the same time utilizes non-natural resources to meet the needs of modern large-scale production. However, the porous structure leads to extremely poor waterproofness of the original base fabric, which needs to be overcome by waterproofing treatment. In the production of ultrafine fiber leather, waterproofing agents are generally added to improve its waterproof performance. However, during the processing, the waterproofing agent tends to float on the surface and is difficult to penetrate into the fabric, resulting in poor waterproofing effect. Summary of the invention
[0004] In order to solve the aforementioned technical problems, the fluorine-free anti-siphon microfiber leather provided by the present invention adopts long-chain alkyl acrylate monomer copolymerization to prepare a fluorine-free waterproof agent, which gives the microfiber leather base cloth a stable low surface energy, thereby avoiding the problem of poor waterproof performance of the microfiber leather base cloth caused by the grid structure. This is specifically achieved through the following technical scheme.
[0005] The present invention discloses a method for preparing fluorine-free anti-siphon microfiber leather, comprising the following steps:
[0006] S1. Weigh non-fluorine acrylate monomer, non-fluorine cross-linked acrylate monomer and monomer having ion supply group in proportion, add surfactant, glacial acetic acid and deionized water thereto, mix all components thoroughly and evenly, and then add emulsifier to emulsify to obtain pre-emulsion;
[0007] S2, adding an initiator and a chain transfer agent to the pre-emulsion, stirring evenly, heating to 60-80° C. and keeping the temperature for 4-5 hours, cooling to room temperature after the reaction is completed, and filtering to obtain a non-fluorinated copolymer emulsion;
[0008] S3, uniformly mixing the polyisocyanate and the chain extender, adding a blocking agent after reacting for 30 minutes and stirring evenly, adding an emulsifier and deionized water after stirring evenly, and homogenizing and emulsifying to obtain an aqueous polyurethane composition;
[0009] S4, uniformly mixing the non-fluorine copolymer emulsion obtained in step S2 and the aqueous polyurethane composition obtained in step S3 to obtain a non-fluorine composition as a product;
[0010] S5, immersing the microfiber leather base fabric into a pool containing the non-fluorine composition for 10 to 15 minutes, then taking it out, squeezing it with a roller, adjusting its liquid rate to 42% to 48%, and then transferring the microfiber leather base fabric to a temperature of 145 to 150° C. and drying it for 8 to 10 minutes to obtain a waterproof base fabric;
[0011] S6. Use a coating machine to evenly apply a layer of polyurethane resin on the release paper, with a coating thickness of 0.12 mm to 0.18 mm. After the coating is completed, transfer the coating to a drying room to slowly dry the coating to obtain the first layer of microfiber leather;
[0012] S7, using a coating machine to evenly apply a layer of polyurethane resin on the first layer of the microfiber leather obtained in step S6, with a coating thickness of 0.15 mm to 0.20 mm, and after the coating is completed, the coating is transferred to a drying room to slowly dry the coating to obtain a second layer of the microfiber leather;
[0013] S8, using a coating machine to evenly apply a layer of polyurethane resin adhesive layer on the second layer of the microfiber leather obtained in step S7, with a coating thickness of 0.18 mm to 0.25 mm, and after the coating is completed, the coating is transferred to a drying room to slowly dry the coating to obtain the third layer of the microfiber leather;
[0014] S9, pressing and bonding the waterproof base fabric in step S5 onto the third layer of the microfiber leather, transferring it to a drying room for slow drying, tearing off the release paper and performing grinding and polishing to obtain a fluorine-free anti-siphon microfiber leather product.
[0015] Preferably, the structural formula of the non-fluorinated acrylate monomer in step S1 is:
[0016]
[0017] Wherein X1 is Cl or Br; Z1 is a saturated hydrocarbon group or a cyclic hydrocarbon group having 1 to 30 carbon atoms; Y1 is a chemical single bond or one or more of -NH-, -NH-CO-, -NHCONH-, -NHCOO-, -NH-SO2-, -NR-, -NR-CO-, -NR-SO2-; R is an alkyl group having 1 to 4 carbon atoms; n1 is an integer of 1 to 20;
[0018] The non-fluorinated acrylate monomer is a mixture of one or more substances conforming to the above structural formula;
[0019] The non-fluorine-linked acrylate monomer in step S1 is a monomer that does not contain fluorine atoms and can be cross-linked, and its structural formula is:
[0020]
[0021] In the formula, X2 is one of (meth)acryloyloxy, (meth)acrylamide and vinyl; Y2 is hydroxyl, epoxy, chloromethyl, blocked isocyanate, amino or carboxyl; and n2 is an integer of 1 to 20.
[0022] Preferably, the monomer having an ion supply group in step S1 is one or more of dimethylaminoethyl (meth)acrylate, (meth)acryloyloxyethyltrimethylammonium chloride, (meth)acrylic acid, maleic acid, itaconic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, vinylbenzene sulfonic acid, and acrylamide-tert-butyl sulfonic acid.
[0023] Preferably, the polyisocyanate in step S3 is one or more of diphenylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, norbornane diisocyanate, allophanate modified product, biuret modified product, isocyanurate modified product, carbodiimide modified product or polyurethane prepolymer.
[0024] Preferably, the chain extender in step S3 is one or more of low molecular weight polyols, polyether polyols, polyester polyols, and polyester polycarbonate polyols.
[0025] Preferably, the blocking agent in step S3 is one or more of N-methylaniline, caprolactam, acetylacetone, methyl ethyl ketone oxime, phenols, imidazoles and pyrazoles.
[0026] Preferably, the mass composition ratio of the non-fluorinated acrylate monomer, the non-fluorinated cross-linked acrylate monomer, and the monomer having an ion supplying group in preparing the pre-emulsion in step S1 is (80% to 90%): (1% to 15%): (0.3% to 5%).
[0027] Preferably, the total mass proportion of the emulsifier and deionized water in the aqueous polyurethane composition in step S3 is 70% to 75%.
[0028] Preferably, the mixing mass ratio of the non-fluorine copolymer emulsion added in step S4 to the aqueous polyurethane composition is 1:(0.2-0.5).
[0029] The present invention also provides the use of the fluorine-free anti-siphon microfiber leather prepared by the preparation method of the fluorine-free anti-siphon microfiber leather in footwear, bags, clothing, accessories, household items, automobile interiors, sports equipment, aerospace and electronic equipment.
[0030] After adopting the above technical solution, the beneficial effects of the present invention are:
[0031] 1. The present invention is based on the copolymerization of long-chain alkyl acrylate monomers to prepare fluorine-free waterproofing agents. The synergistic effect between the polar side groups and the long-chain alkyl groups in the copolymer structure affects the activity of the silicon-containing side groups, which is beneficial to inhibit the silicon-containing side groups enriched on the outermost surface from returning to the polymer body, giving the microfiber leather base fabric a more durable and stable low surface energy, making it have better waterproof performance;
[0032] 2. After the non-fluorine composition obtained by mixing the non-fluorine copolymer emulsion and the waterborne polyurethane composition is impregnated with the microfiber leather base fabric, the fluorine-free small molecular chain structure in the composition fills the larger pores and holes of the microfiber leather base fabric fibers, closes the rising channel of water molecules, and effectively prevents water from climbing upward through the pores, thereby achieving an anti-siphon effect;
[0033] 3. The polymer of the present invention avoids the use of fluorine-containing acrylate monomers, is more environmentally friendly, is more likely to be favored by consumers, and has high commercial value. DETAILED DESCRIPTION
[0034] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.
[0035] An embodiment of the present invention provides a method for preparing fluorine-free anti-siphon microfiber leather, comprising the following steps:
[0036] S1. Weigh non-fluorine acrylate monomer, non-fluorine cross-linked acrylate monomer and monomer having ion supply group in proportion, add surfactant, glacial acetic acid and deionized water thereto, mix all components thoroughly and evenly, and then add emulsifier to emulsify to obtain pre-emulsion.
[0037] The structural formula of the non-fluorinated acrylate monomer is:
[0038]
[0039] In the formula, X1 is Cl or Br; Z1 is a saturated hydrocarbon group or a cyclic hydrocarbon group having 1 to 30 carbon atoms; Y1 is a chemical single bond or one or more of -NH-, -NH-CO-, -NHCONH-, -NHCOO-, -NH-SO2-, -NR-, -NR-CO-, -NR-SO2-, R is an alkyl group having 1 to 4 carbon atoms; n1 is an integer from 1 to 20.
[0040] The non-fluorinated acrylate monomer is a mixture of one or more substances conforming to the above structural formula.
[0041] The non-fluorine cross-linked acrylate monomer is a monomer that does not contain fluorine atoms and can be cross-linked, and its structural formula is:
[0042]
[0043] In the formula, X2 is one of (meth)acryloyloxy, (meth)acrylamide and vinyl; Y2 is hydroxyl, epoxy, chloromethyl, blocked isocyanate, amino or carboxyl; and n2 is an integer of 1 to 20.
[0044] The non-fluorine-linked acrylate monomer can also be a polyalkenyl polyether or polyester containing at least two polymerizable ethylenically unsaturated double bonds. This type of non-fluorine-linked acrylate monomer is an etherification reaction product of allyl alcohol or acrylic acid and a linear or branched polyol having 2 to 15 carbon atoms.
[0045] Wherein, the polyol is one or more of sucrose, hydroxypropyl cyclotetrasiloxane, polyhydroxypropyl polysilsesquioxane, pentaerythritol, dipentaerythritol, trimethylolpropane and its dimer, triethylolpropane and its dimer.
[0046] The above two types of non-fluorine cross-linked acrylate monomers can be used alone or together to synthesize the non-fluorine composition.
[0047] Among them, polyalkenyl polyether or polyester containing polymerizable ethylenically unsaturated double bonds is used as non-fluorine cross-linked acrylate monomers. Since such compounds contain alkenyl groups (carbon-carbon double bonds), and the alkenyl double bonds can participate in various chemical reactions such as free radical polymerization and addition reactions, such compounds have high reactivity; in addition, the ether bonds (-O-) contained in the chain segments can also give the compound good solubility and stability.
[0048] Therefore, the above-mentioned polyalkenyl polyether or polyester containing at least two polymerizable ethylenically unsaturated double bonds is used as a non-fluorine cross-linked acrylate monomer. Due to its high reactivity, good solubility and stability, when it undergoes polymerization reaction or addition reaction with the non-fluorine acrylate monomer, the reaction is more efficient and thorough; in addition, the reaction synthetic material is more easily miscible with the aqueous polyurethane composition, ensuring the good stability of the mixture.
[0049] The monomer having an ion supply group is one or more of dimethylaminoethyl (meth)acrylate, (meth)acryloyloxyethyltrimethylammonium chloride, (meth)acrylic acid, maleic acid, itaconic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, vinylbenzene sulfonic acid, and acrylamide-tert-butyl sulfonic acid.
[0050] Wherein, the emulsifier is one or more of fatty acid soap, alkyl sulfate, alkyl benzene sulfonate, phosphate, and quaternary ammonium salt.
[0051] The mass composition ratio of the added non-fluorine acrylate monomer, non-fluorine cross-linked acrylate monomer, and monomer having an ion supply group is (80% to 90%): (1% to 15%): (0.3% to 5%).
[0052] The mass ratio of the total mass of the added non-fluorine acrylate monomer, the non-fluorine cross-linked acrylate monomer, and the monomer having an ion supply group to the added emulsifier is 1:(0.08-0.12).
[0053] Among them, the mass proportion of deionized water in the above pre-emulsion is 70% to 75%.
[0054] Wherein, the surfactant is one or more of potassium monododecyl phosphate, disodium lauryl sulfosuccinate, fatty alcohol polyoxyethylene ether, and sodium dioctyl maleate sulfonate.
[0055] The mass ratio of the total mass of the added non-fluorine acrylate monomer, the non-fluorine cross-linked acrylate monomer, and the monomer having an ion supply group to the added surfactant and glacial acetic acid is 1:(0.001-0.02):(0.0005-0.001).
[0056] S2, adding an initiator and a chain transfer agent to the pre-emulsion, stirring evenly, heating to 60-80° C. and keeping the temperature for 4-5 hours, cooling to room temperature after the reaction is completed, and filtering to obtain a non-fluorinated copolymer emulsion;
[0057] Wherein, the initiator is one or more of dimethyl azobisisobutyrate, azobisisobutyronitrile, azobisisoheptanenitrile, tert-butyl hydroperoxide, and benzoyl peroxide.
[0058] The chain transfer agent is one or more of dodecyl mercaptan, isobutyl mercaptan, tert-butyl mercaptan, hexadecyl mercaptan, tetradecyl mercaptan, methyl mercaptan, ethyl mercaptan, propyl mercaptan and butyl mercaptan.
[0059] The molar ratio of the total mass of the added non-fluorinated acrylate monomer, the non-fluorinated cross-linked acrylate monomer, and the monomer having an ion supply group to the added initiator and chain transfer agent is 1:(0.001-0.02):(0.0005-0.001).
[0060] Through the above steps, the non-fluorine copolymer emulsion prepared by copolymerizing the non-fluorine acrylate monomer, the non-fluorine cross-linked acrylate monomer and the monomer with the ion supply group is used as a component of the non-fluorine composition. The main reason is that the carbon-carbon double bond in the non-fluorine acrylate monomer is very active, especially under the condition of the monomer with the ion supply group, it is easy to undergo addition reaction and free radical polymerization. Therefore, after the above three monomer substances are mixed, the non-fluorine acrylate monomer undergoes ion cross-linking and free radical cross-linking under the condition of the ion supply group monomer, and together with the non-fluorine cross-linked acrylate monomer in the mixture, a polymer compound with a three-dimensional network structure is formed, so that the obtained polymer has better physical properties such as strength, wear resistance and heat resistance.
[0061] S3, uniformly mixing the polyisocyanate and the chain extender, adding a blocking agent after reacting for 30 minutes and stirring evenly, adding an emulsifier and deionized water after stirring evenly, and homogenizing and emulsifying to obtain an aqueous polyurethane composition;
[0062] The polyisocyanate is one or more of diphenylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, norbornane diisocyanate, allophanate modified product, biuret modified product, isocyanurate modified product, carbodiimide modified product or polyurethane prepolymer.
[0063] Wherein, the chain extender is one or more of low molecular weight polyols, polyether polyols, polyester polyols, and polyester polycarbonate polyols.
[0064] Wherein, the emulsifier is one or more of fatty acid soap, alkyl sulfate, alkyl benzene sulfonate, phosphate, and quaternary ammonium salt.
[0065] Wherein, the blocking agent is one or more of N-methylaniline, caprolactam, acetylacetone, methyl ethyl ketone oxime, phenols, imidazoles and pyrazoles.
[0066] Wherein, the blocked isocyanate accounts for 25% to 30% by mass in the aqueous polyurethane composition.
[0067] Among them, the homogenization emulsification process uses high shear force or high-pressure homogenizer and other equipment to homogenize the emulsion, so that the prepolymer particles are evenly dispersed in the water to form a stable water-based polyurethane emulsion.
[0068] The mass ratio of the added polyisocyanate, chain extender and blocking agent is 1: (0.06-0.1): (0.06-0.1).
[0069] The mass ratio of the total mass of the added polyisocyanate, chain extender and blocking agent to the mass ratio of the added emulsifier is 1:(0.08-0.12).
[0070] In the present invention, the isocyanate groups contained in the polyisocyanate molecules are easily subjected to addition reaction with the hydroxyl groups contained in the low molecular weight polyols, so that the above two compounds react to form a polyurethane prepolymer or a cross-linked network structure, and the blocking agent is mainly used as an intermediate and solvent for organic synthesis in the process, and is fully integrated with the polyurethane prepolymer or the cross-linked network structure and other reaction materials to make them more homogenized, and is also convenient for integration with the non-fluorine copolymer emulsion, thereby preparing the non-fluorine composition.
[0071] In the present invention, an aqueous polyurethane composition is used as one of the main components of the non-fluorine composition, based on its characteristics of being pollution-free, safe and reliable, having excellent mechanical properties and good compatibility. The aqueous polyurethane composition uses water as a solvent, has low cost, is easy to operate, and can be fully mixed with a variety of aqueous resins to enable the product to have higher wear resistance and impact resistance. As a raw material for microfiber leather, it can make the product tougher and softer to the touch.
[0072] S4, uniformly mixing the non-fluorine copolymer emulsion obtained in step S2 and the aqueous polyurethane composition obtained in step S3 to obtain a non-fluorine composition as a product;
[0073] The mass ratio of the added non-fluorinated copolymer emulsion to the aqueous polyurethane composition is 1:(0.2-0.5).
[0074] S5, immersing the microfiber leather base fabric into a pool containing the non-fluorine composition for 10 to 15 minutes, then taking it out, squeezing it with a roller, adjusting its liquid rate to 42% to 48%, and then transferring the microfiber leather base fabric to a temperature of 145 to 150° C. and drying it for 8 to 10 minutes to obtain a waterproof base fabric;
[0075] The macromolecular chain structure and hydrophobic groups in the non-fluorine composition are used to form a film on the surface of the microfiber leather base fabric fibers to reduce the surface tension; the fluorine-free small molecule chain structure in the non-fluorine composition is used to fill the larger bubbles and holes in the microfiber leather base fabric fibers to close the rising channel of water molecules; therefore, based on the above-mentioned non-fluorine composition, the anti-siphon effect of the microfiber leather base fabric is achieved.
[0076] S6. Use a coating machine to evenly apply a layer of polyurethane resin on the release paper, with a coating thickness of 0.12 mm to 0.18 mm. After the coating is completed, transfer the coating to a drying room to slowly dry the coating to obtain the first layer of microfiber leather;
[0077] The polyurethane resin is formed by the addition polymerization of polyisocyanates (such as diisocyanates) and polyols, so it has excellent wear resistance, adhesion, chemical resistance, vibration resistance and fatigue resistance. It is a commonly used technical means in this field and will not be described here.
[0078] S7, using a coating machine to evenly apply a layer of polyurethane resin on the first layer of the microfiber leather obtained in step S6, with a coating thickness of 0.15 mm to 0.20 mm, and after the coating is completed, the coating is transferred to a drying room to slowly dry the coating to obtain a second layer of the microfiber leather;
[0079] S8, using a coating machine to evenly apply a layer of polyurethane resin adhesive layer on the second layer of the microfiber leather obtained in step S7, with a coating thickness of 0.18 mm to 0.25 mm, and after the coating is completed, the coating is transferred to a drying room to slowly dry the coating to obtain the third layer of the microfiber leather;
[0080] The drying temperature in step S6, step S7 and step S8 is 70° C. to 120° C., thereby ensuring the bonding quality of the polyurethane resin.
[0081] S9, pressing and bonding the waterproof base fabric in step S5 onto the third layer of the microfiber leather, transferring it to a drying room for slow drying, tearing off the release paper and performing grinding and polishing to obtain a fluorine-free anti-siphon microfiber leather product.
[0082] Among them, the torn release paper can be recycled after cleaning, thereby reducing the production cost to a certain extent.
[0083] Among them, the pressing pressure in step S9 is 0.3-0.4 MPa, the pressing time is 5-10 min, to ensure the bonding quality of the waterproof base fabric and the third layer of microfiber leather, and the subsequent drying temperature is 100°C-140°C.
[0084] The fluorine-free anti-siphon microfiber leather prepared by the above method can be applied in multiple fields, among which the fluorine-free anti-siphon microfiber leather can be used for the preparation of footwear, for example, as the upper and sole materials of sports shoes, casual shoes, and leather shoes; it can also be used for the preparation of luggage products, such as the fabric or outer leather material of handbags, backpacks, and wallets.
[0085] Among them, the fluorine-free anti-siphon microfiber leather can also be used in clothing production, such as fabrics for coats, pants, and skirts, which are waterproof, breathable, soft and comfortable.
[0086] The fluorine-free anti-siphon microfiber leather can also be used to make accessories, such as being used as fabric to make ties, scarves, and hats.
[0087] Among them, the fluorine-free anti-siphon microfiber leather can also be used to make car interiors, such as as a covering fabric for car seats, steering wheels, and door panels, to improve the texture of the car and enhance the driving experience.
[0088] The fluorine-free anti-siphon microfiber leather can also be used to make sports equipment, such as the outer cover of footballs, basketballs, and volleyballs, thereby improving the stability of ball products; sled cushions or bicycle cushions, to improve the comfort of athletes.
[0089] Among them, the fluorine-free anti-siphon microfiber leather can also be used in the aerospace field, such as for covering aircraft seats and luggage racks, thereby improving the riding comfort of passengers.
[0090] Among them, the fluorine-free anti-siphon microfiber leather can also be used in the field of electronic equipment, such as as a protective cover for mobile phones, tablet computers or other high-end electronic devices to improve the safety performance of the product.
[0091] As a further explanation of the present invention, after the fluorine-free anti-siphon microfiber leather is prepared by the above method, it is necessary to use a standard method to test its water-repellent effect.
[0092] The standard method is to use the national standard GB / T4745-2012 to examine the water repellent effect, and the specific method is:
[0093] Cut a 18×18cm finished fabric and stretch it on the clamp and place it at an angle of 45°. Set a nozzle 150mm above it and quickly spray 250ml of water on the inclined fabric within 25-30s. After spraying, take out the fabric and knock it horizontally with the front side facing down twice to observe the experimental wetting degree. Then use text description and compare with standard pictures to evaluate its grade. The grade distribution is shown in the following table:
[0094] Water level Description of water contact Level 0 The entire sample surface is completely wetted Level 1 Complete wetting of the exposed surface Level 1-2 Wetting beyond the spray point, the wetted area exceeds half of the sprayed surface Level 2 Wetting beyond the spray point, the wetted area is about half of the sprayed surface Level 2-3 Wetting beyond the spray point, the wetted area is less than half of the sprayed surface Level 3 Wetting of the sample surface at the spray point Level 3-4 The sample surface is wetted at equal to or less than half of the spray points Level 4 The sample surface is wetted at sporadic spray points Level 4-5 The sample surface is not wetted, with a small amount of water droplets Level 5 No water droplets or wetting on the specimen surface
[0095] To facilitate understanding of the present invention, several embodiments of the present invention are given below.
[0096] Example 1
[0097] S1, after 850g of non-fluorine acrylate monomer, 100g of non-fluorine cross-linked acrylate monomer and 50g of styrene sulfonic acid are uniformly mixed, 2g of monododecyl potassium phosphate, 1g of glacial acetic acid and 3000g of deionized water are added to the mixture, and after the components are fully mixed, 100g of ammonium dodecyl sulfate is added to obtain a pre-emulsion;
[0098] Among them, the molecular formula of the non-fluorinated acrylate monomer is:
[0099]
[0100] Wherein, the molecular formula of the non-fluorine cross-linked acrylate monomer is:
[0101]
[0102] S2. Add 2 g of benzoyl peroxide and 1 g of dodecyl mercaptan to the pre-emulsion, stir evenly, heat to 70° C. and keep warm for 4.5 hours. After the reaction is completed, cool to room temperature and filter to obtain a non-fluorine copolymer emulsion.
[0103] S3, 600g of diphenylmethane diisocyanate and 50g of polyether polyol were uniformly mixed, and after reacting for 30 minutes, 50g of acetylacetone was added and stirred evenly, and after stirring evenly, 70g of ammonium dodecyl sulfate and 2000g of deionized water were added, and the mixture was fully stirred to obtain an aqueous polyurethane composition.
[0104] S4. Take 2000 g of the non-fluorine copolymer emulsion obtained in step S2 and 1000 g of the aqueous polyurethane composition obtained in step S3, respectively, and mix them thoroughly to obtain a non-fluorine composition.
[0105] S5. Immerse a 30×30 cm microfiber leather base fabric in the non-fluorine composition obtained in step S4 for 10 minutes. After the impregnation, squeeze it with a roller to adjust the liquid rate to 45%. Finally, transfer it to a temperature environment of 150° C. and dry it for 10 minutes to obtain a waterproof base fabric.
[0106] S6. Use a coating machine to evenly apply a layer of polyurethane resin on the release paper with a coating thickness of 0.15 mm. After the coating is completed, transfer the coating to a drying room at 100° C. and slowly dry the coating to obtain the first layer of microfiber leather;
[0107] S7, using a coating machine to evenly apply a layer of polyurethane resin on the first layer of the microfiber leather obtained in step S6, with a coating thickness of 0.18 mm, and after the coating is completed, transfer the coating to a drying room at 100° C. and slowly dry the coating to obtain a second layer of the microfiber leather;
[0108] S8, using a coating machine to evenly apply a layer of polyurethane resin adhesive layer on the second layer of the microfiber leather obtained in step S7, with a coating thickness of 0.20 mm, and after the coating is completed, transfer the coating to a drying room at 100° C. and slowly dry the coating to obtain the third layer of the microfiber leather;
[0109] S9. Bond the waterproof base fabric in step S5 to the third layer of the microfiber leather under a pressing pressure of 0.4 MPa, transfer it to a drying room at 120° C. for slow drying, tear off the release paper and perform grinding and polishing to obtain a fluorine-free anti-siphon microfiber leather product.
[0110] S10. Cut 18×18 cm of the fluorine-free anti-siphon microfiber leather obtained in step S9 and place it on a clamp and tilt it at 45 degrees. Set a nozzle 150 mm above it and spray 250 ml of water on the microfiber leather within 25 seconds. After spraying, take out the microfiber leather, knock it horizontally twice with the front side facing down, and observe its wetting degree: the surface of the sample is not wetted, but there are a small amount of water droplets, and its water-wetting level is determined to be level 4 to 5.
[0111] Example 2
[0112] This embodiment is based on the embodiment 1, and the heating temperature and the holding time in step S2 are adjusted, specifically:
[0113] S2. Add 2 g of benzoyl peroxide and 1 g of dodecyl mercaptan to the pre-emulsion, stir evenly, heat to 80° C. and keep warm for 5 hours. After the reaction is completed, cool to room temperature and filter to obtain a non-fluorine copolymer emulsion.
[0114] The remaining steps and conditions are the same as in Example 1.
[0115] The wettability of the finally obtained fluorine-free anti-siphon microfiber leather is that the surface of the sample is not wetted, but there are a small amount of water droplets, and its water-wetting level is determined to be 4 to 5.
[0116] Example 3
[0117] This embodiment is based on the embodiment 1, and the addition amount of the waterborne polyurethane composition in step S4 is adjusted to 800g, specifically:
[0118] S4. Take 2000 g of the non-fluorine copolymer emulsion obtained in step S2 and 800 g of the aqueous polyurethane composition obtained in step S3, respectively, and mix them thoroughly to obtain a non-fluorine composition.
[0119] The other steps and conditions are the same as those in Example 1.
[0120] The wettability of the finally obtained fluorine-free anti-siphon microfiber leather was that there were sporadic spray points on the surface of the sample, and its water-wetting grade was determined to be level 4.
[0121] Example 4
[0122] This embodiment is based on the embodiment 1, and the impregnation time in step S5 is adjusted to 15 minutes, specifically:
[0123] S5. Immerse a 30×30 cm microfiber leather base fabric in the non-fluorine composition obtained in step S4 for 15 minutes. After the impregnation, squeeze it with a roller to adjust the liquid rate to 45%. Finally, transfer it to a temperature environment of 150° C. and dry it for 10 minutes to obtain a waterproof base fabric.
[0124] The other steps and conditions are the same as those in Example 1.
[0125] The wettability of the finally obtained fluorine-free anti-siphon microfiber leather is that the surface of the sample is not wetted, but there are a small amount of water droplets, and its water-wetting level is determined to be 4 to 5.
[0126] According to the embodiments of the present invention as described above, these embodiments do not describe all the details in detail, nor do they limit the invention to specific embodiments. Obviously, many modifications and changes can be made based on the above description. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can make good use of the present invention and the modified use based on the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing fluorine-free anti-siphon microfiber leather, characterized in that: The following steps are involved: S1. Weigh non-fluorine acrylate monomer, non-fluorine cross-linked acrylate monomer and monomer having ion supply group in proportion, add surfactant, glacial acetic acid and deionized water thereto, mix all components thoroughly and evenly, and then add emulsifier to emulsify to obtain pre-emulsion; S2, adding an initiator and a chain transfer agent to the pre-emulsion, stirring evenly, heating to 60-80° C. and keeping the temperature for 4-5 hours, cooling to room temperature after the reaction is completed, and filtering to obtain a non-fluorinated copolymer emulsion; S3, uniformly mixing the polyisocyanate and the chain extender, adding a blocking agent after reacting for 30 minutes and stirring evenly, adding an emulsifier and deionized water after stirring evenly, and homogenizing and emulsifying to obtain an aqueous polyurethane composition; S4, uniformly mixing the non-fluorine copolymer emulsion obtained in step S2 and the aqueous polyurethane composition obtained in step S3 to obtain a non-fluorine composition as a product; S5, immersing the microfiber leather base fabric into a pool containing the non-fluorine composition for 10 to 15 minutes, then taking it out, squeezing it with a roller, adjusting its liquid rate to 42% to 48%, and then transferring the microfiber leather base fabric to a temperature of 145 to 150° C. and drying it for 8 to 10 minutes to obtain a waterproof base fabric; S6. Use a coating machine to evenly apply a layer of polyurethane resin on the release paper, with a coating thickness of 0.12 mm to 0.18 mm. After the coating is completed, transfer the coating to a drying room to slowly dry the coating to obtain the first layer of microfiber leather; S7, using a coating machine to evenly apply a layer of polyurethane resin on the first layer of the microfiber leather obtained in step S6, with a coating thickness of 0.15 mm to 0.20 mm, and after the coating is completed, the coating is transferred to a drying room to slowly dry the coating to obtain a second layer of the microfiber leather; S8, using a coating machine to evenly apply a layer of polyurethane resin adhesive layer on the second layer of the microfiber leather obtained in step S7, with a coating thickness of 0.18 mm to 0.25 mm, and after the coating is completed, the coating is transferred to a drying room to slowly dry the coating to obtain the third layer of the microfiber leather; S9, pressing and bonding the waterproof base fabric in step S5 onto the third layer of the microfiber leather, transferring it to a drying room for slow drying, tearing off the release paper and performing grinding and polishing to obtain a fluorine-free anti-siphon microfiber leather product; The structural formula of the non-fluorinated acrylate monomer in step S1 is: Wherein X1 is Cl or Br; Z1 is a saturated hydrocarbon group or a cyclic hydrocarbon group having 1 to 30 carbon atoms; Y1 is a chemical single bond or one or more of -NH-, -NH-CO-, -NHCONH-, -NHCOO-, -NH-SO2-, -NR-, -NR-CO-, -NR-SO2-; R is an alkyl group having 1 to 4 carbon atoms; n1 is an integer of 1 to 20; The non-fluorinated acrylate monomer is a mixture of one or more substances conforming to the above structural formula; The non-fluorine-linked acrylate monomer in step S1 is a monomer that does not contain fluorine atoms and can be cross-linked, and its structural formula is: Wherein X2 is one of (meth)acryloyloxy, (meth)acrylamide and vinyl; Y2 is hydroxyl, epoxy, chloromethyl, blocked isocyanate, amino or carboxyl; n2 is an integer of 1 to 20; The monomer having an ion supply group in step S1 is one or more of dimethylaminoethyl (meth)acrylate, (meth)acryloyloxyethyltrimethylammonium chloride, (meth)acrylic acid, maleic acid, itaconic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, vinylbenzene sulfonic acid, and acrylamide-tert-butyl sulfonic acid.
2. The method for preparing the fluorine-free anti-siphon microfiber leather according to claim 1, characterized in that: The polyisocyanate in step S3 is one or more of diphenylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, norbornane diisocyanate, allophanate modified product, biuret modified product, isocyanurate modified product, carbodiimide modified product or polyurethane prepolymer.
3. The method for preparing the fluorine-free anti-siphon microfiber leather according to claim 1, characterized in that: The chain extender in step S3 is one or more of low molecular weight polyols, polyether polyols, polyester polyols, and polyester polycarbonate polyols.
4. The method for preparing fluorine-free anti-siphon microfiber leather according to claim 1, characterized in that: The blocking agent in step S3 is one or more of N-methylaniline, caprolactam, acetylacetone, methyl ethyl ketone oxime, phenols, imidazoles and pyrazoles.
5. The method for preparing fluorine-free anti-siphon microfiber leather according to claim 1, characterized in that: The mass composition ratio of the non-fluorinated acrylate monomer, the non-fluorinated cross-linked acrylate monomer, and the monomer having an ion supplying group in preparing the pre-emulsion in step S1 is (80% to 90%): (1% to 15%): (0.3% to 5%).
6. The method for preparing fluorine-free anti-siphon microfiber leather according to claim 1, characterized in that: The total mass proportion of the emulsifier and deionized water in the aqueous polyurethane composition in step S3 is 70% to 75%.
7. The method for preparing fluorine-free anti-siphon microfiber leather according to claim 1, characterized in that: The mixing mass ratio of the non-fluorine copolymer emulsion added in step S4 to the aqueous polyurethane composition is 1:(0.2-0.5).
8. Application of the fluorine-free anti-siphon microfiber leather prepared by the method for preparing the fluorine-free anti-siphon microfiber leather according to any one of claims 1 to 7 in footwear, bags, clothing, accessories, household items, automotive interiors, sports equipment, aerospace and electronic equipment.
Citation Information
Patent Citations
Method for producing superfine fiber special safety shoe leather
CN105463870A
Fluoride-free waterproof agent and preparation method thereof
CN113279257A
High water repellency artificial leather and its manufacturing method
CN1814906A